Calling for equitable access to the Canadian labor market: Exploring the challenges of international graduate students in Canada - Nguyen, Trung Tu; Sharma, Manu (Journal of International Students, 2024)
In this paper, we identify the main challenges faced by international graduate students seeking employment in the Canadian labor market after completing Canadian Master of Education programs. We approach this issue from our combined perspectives: a professor of higher education and a recent international graduate with a Master of Education program. Drawing on the theoretical framework Responsibility of the University in Employability (RUE) (López‐Miguens et al., 2021), we argue that universities play a significant role in preparing international students for successful integration into the Canadian workforce. After conducting a thematic analysis of the relevant literature, we identify the five most common key challenges faced by international students: racialized complexities of a credential regime, problems of deskilling and devaluation of immigrants, the triple glass effect, foreign accent bias, and a lack of soft skills according to the Canadian norm.